Ecosocial transition for healthy cities: insights from a botanical garden in Istanbul - Heyik, Muhammet Ali; Atmaca, Ahmet Bircan; Caliskan, Zuhal; Romero-Martinez, Jose Maria (TAYLOR & FRANCIS LTD, 2025)
This study investigates chronic urban challenges through an ecosocial lens, focusing on a botanical garden located at highway intersections in Istanbul. Multiple data sources were combined, including historical analyses of the site, visitor statistics, site observations, interviews, and systematic field measurements. These datasets were examined at two scales: the broader urban transformation and the site-scale evolution from afforestation of fragmented highway residuals to a botanical garden threatened by mega-projects. Historical change was assessed longitudinally using the actor-network mapping technique. Fieldwork at selected points captured site heterogeneity, with repeated measurements under seasonal extremes to assess environmental conditions. Findings demonstrate the garden's capacity to mitigate highway-induced pollution, while enhancing biodiversity conservation, environmental education, and public well-being. However, its incorporation into growth-driven urbanization raises concerns of (eco)gentrification and shortcomings in convivial conservation. To contextualize these issues, a cross-case analysis was undertaken to identify main barriers to ecosocial transition. By critically engaging with green growth paradigms, the study contrasts post-growth and ecocentric approaches, advocating resource-efficient, community-driven planning that prioritizes high-need areas while curbing competition-driven overdevelopment. Ultimately, the results underscore the importance of embedding nature's rights into urban planning, highlighting ecological integrity, circularity, and social equity as essential conditions for achieving a just ecosocial transition.
Keywords: Ecosocial transition, healthy cities; mega-projects, gentrification; Istanbul; botanical garden; SOUNDSCAPE; QUALITY; Public, Environmental & Occupational Health; Urban Studies